Clinical imaging physics : current and emerging practice - Samei, Ehsan; Pfeiffer, Douglas E. (Hoboken, NJ : Wiley-Blackwell, 2020)
"Six primary developments are converging today to raise radiologic imaging to an ever more prominent role in biomedical and medical research and in the clinical practice of medicine: (1) Increasing sophistication of the biological questions that can be addressed as knowledge expands and understanding grows about the complexity of the human body and its static and dynamic properties; (2) Ongoing evolution of imaging technologies and the increasing breadth and depth of the questions that these technologies can address at ever more fundamental levels; (3) Accelerating advances in computer technology and information networking that support imaging advances such as three- and four-dimensional representations, superposition of images from different devices, creation of virtual-reality environments, and transportation of images to remote sites in real time; (4) Growth of massive amounts of information about patients that can best be compressed and expressed through the use of images; (5) Entry into research and clinical medicine of young persons who are highly facile with computer technologies and comfortable with images as the principal pathway to information acquisition and display; and (6) Growing importance of images as effective means to convey information in visually-oriented developed cultures. A major challenge confronting medical imaging now is the need to efficiently exploit this convergence of developments to accelerate biological and medical imaging toward the realization of its true potential. Central to all of these developments is clinical medical physics, a growing field whose importance in the clinical practice of radiology is especially strong. Around the world, tens of thousands imaging physicists are employed by healthcare facilities or consulting groups. These individuals are tasked with properly setting up and optimally operating medical imaging devices to achieve the highest diagnostic performance and patient safety. They also constantly consult directly with radiologists and other clinical imaging staff on day to day issues ranging from basic technology to image refinement, interpretation, and diagnostics. Despite a substantial knowledgebase on the practice of medical physics in clinical imaging, until now medical physicists and radiologists have not had the benefit of a single-source reference and textbook on the science and clinical application of medical physics"--
What is clinical imaging physics? -- Part I. Radiography. Clinical radiography physics: perspective -- Clinical radiography physics: state of practice -- Clinical radiography physics: emerging practice -- Part II. Mammography. Clinical mammography physics: perspective -- Clinical mammography physics: state of practice -- Clinical mammography physics: emerging practice -- Part III. Fluoroscopy. Clinical fluoroscopy physics: perspective -- Clinical fluoroscopy physics: state of practice -- Clinical fluoroscopy physics: emerging practice -- Part IV. Computed tomography. Clinical CT physics: perspective -- Clinical CT physics: state of practice -- Clinical CT physics: emerging practice -- Part V. Nuclear imaging. Clinical nuclear imaging physics: perspective -- Clinical nuclear imaging physics: current and emerging practice -- Part VI. Ultrasonography. Clinical ultrasonography physics: perspective -- Clinical ultrasonography physics: state of practice -- Clinical ultrasonography physics: emerging practice -- Part VII. Magnetic resonance imaging. Clinical MRI physics: perspective -- Clinical MRI physics: state of practice -- Clinical MRI physics: emerging practice -- Part VIII. Imaging informatics.Clinical physics in it: perspective -- Clinical physics in informatics display: current and emerging practice -- Clinical physics in imaging informatics: current and emerging practice -- Abbreviations
BIBINDX
Keywords: Diagnostic imaging -- Methodology; Medical physics; Diagnostic Imaging -- methods; Biophysical Phenomena; Electronic books